A Stylistic Analysis of the Saharan French colonial architecture in southern Algeria - Benghida, Nassiba; Sriti, Leila; Femmam, Asma; Saouli, Sarra; Mekki, Sana (Technium Social Sciences Journal, 2023)
This work undertakes a study of the colonial architecture produced in southern Algeria during the 19th and 20th centuries. The comparison of the colonial architecture as it is manifested in public buildings in the north and south of the country will make it possible to grasp the specific characteristics of the architectural language developed in Saharan cities during the colonial period from 1832 to 1962. More precisely, the research endeavours to reconstruct, in a chronological manner, the conditions of production, the modalities of evolution of this architecture and the diversity of its formal attributes. To this end, a historical-analytical approach has been applied to a sample of buildings representative of the French presence in Algeria. In particular, the analysis focused on their architectural features with the intention of characterising the French imperialism formal and stylistic expressions which are rooted in eighteenth-century orientalism. The results show that the emphasis on 'indigenous' culture promoted by Governor Jonnart in the early 20th century, which was crowned by the adoption of the architectural orientalism as an official style often emanated from a concerted policy to symbolise France’s presence, power, and domination in the colonised territory. Additionally, the study highlighted the features related to the stylistic expression of the public facades through the identification of the architectural and decorative elements used in their design. Finally, it appeared that official architecture in the north was generally expressed through a single style that was successively neo-classical, art deco and neo-Moorish. In the south, however, colonial architecture was more nuanced and clearly influenced by the local Saharan context and the vernacular built environment, although the concept of vernacular architecture has been implemented just as mere rhetoric. Therefore, the colonial architecture generated in the southern territories cannot be considered as strictly imported or exogenous, as was the case for the north, but rather as the result of crossbreeding between vernacular, occidental and sub-Saharan African architectures.